Linked symptom monitoring and depression treatment programmes for specialist cancer services: protocol for a mixed-methods implementation study. Issue 6 (2nd July 2017) - Wanat, Marta; Walker, Jane; Burke, Katy; Sevdalis, Nick; Richardson, Alison; Mulick, Amy; Frost, Chris; Sharpe, Michael
Abstract : Introduction: There is growing awareness that cancer services need to address patients' well-being as well as treating their cancer. We developed systematic approaches to (1) monitoring patients' symptoms including depression using a 'Symptom Monitoring Service' and (2) providing treatment for those with major depression using a programme called 'Depression Care for People with Cancer'. Used together, these two programmes were found to be highly effective and cost-effective in clinical trials. The overall aims of this project are to: (1) study the process of introducing these programmes into routine clinical care in a large cancer service, (2) identify the challenges associated with implementation and how these are overcome, (3) determine their effectiveness in a routine non-research setting and (4) describe patients' and clinicians' experience of the programmes. Methods and analysis: This is a mixed-methods longitudinal implementation study. We will study the process of implementation in three phases (April 2016–December 2018): 'Pre-implementation' (setting up of the new programmes), 'Early Implementation' (implementation of the programmes in a small number of clinics) and 'Implementation and Maintenance' (implementation in the majority of clinics). We will use the following methods of data collection: (1) contemporaneous logs of the implementation process, (2) interviews with healthcare professionals and managers, (3) interviews with patients and (4) routinely collected clinical data. Ethics and dissemination: The study has been reviewed by a joint committee of Oxford University Hospitals National Health Service Foundation Trust Research and Development Department and the University of Oxford's Clinical Trials and Research Governance Department and judged to be service evaluation, not requiring ethics committee approval. The findings of this study will guide the scaling up implementation of the programmes across the UK and will enable us to construct an implementation toolkit. We will disseminate our findings in publications and at relevant national and international conferences.